Analysis of Process Parameters for Porosity in Porous NiTi Implants - Tosun, Gul; Tosun, Nihat (Taylor & Francis Inc, 2012)
This article presents optimization of process parameters for the porosity in NiTi alloy produced as implant material by self-propagating high-temperature synthesis (SHS) method. The experiments were conducted under the different process parameters, namely, compaction pressure, preheating temperature, and heating rate. A plan of experiments based on the Taguchi method was designed. The level of importance of the process parameters is determined by using analysis of variance (ANOVA). The optimum process parameter combination was obtained by using the analysis of signal-to-noise (S/N) ratio. Through statistical analysis of response variables and S/N ratios, the determined significant factors were the heating rate and pressure. By using regression analysis method, the variation of the porosity in the implant with production parameters is mathematically modeled.
Keywords: ANOVA; Modeling; NiTi; Porosity